Mitochondria as novel mediators linking gut microbiota to atherosclerosis that is ameliorated by herbal medicine: A review - Li, Yujuan; Yang, Shengjie; Jin, Xiao; Li, Dan; Lu, Jing; Wang, Xinyue; Wu, Min (Frontiers in Pharmacology, 2023)
Atherosclerosis (AS) is the main cause of cardiovascular disease (CVD) and is characterized by endothelial damage, lipid deposition, and chronic inflammation. Gut microbiota plays an important role in the occurrence and development of AS by regulating host metabolism and immunity. As human mitochondria evolved from primordial bacteria have homologous characteristics, they are attacked by microbial pathogens as target organelles, thus contributing to energy metabolism disorders, oxidative stress, and apoptosis. Therefore, mitochondria may be a key mediator of intestinal microbiota disorders and AS aggravation. Microbial metabolites, such as short-chain fatty acids, trimethylamine, hydrogen sulfide, and bile acids, also affect mitochondrial function, including mtDNA mutation, oxidative stress, and mitophagy, promoting low-grade inflammation. This further damages cellular homeostasis and the balance of innate immunity, aggravating AS. Herbal medicines and their monomers can effectively ameliorate the intestinal flora and their metabolites, improve mitochondrial function, and inhibit atherosclerotic plaques. This review focuses on the interaction between gut microbiota and mitochondria in AS and explores a therapeutic strategy for restoring mitochondrial function and intestinal microbiota disorders using herbal medicines, aiming to provide new insights for the prevention and treatment of AS.